Optimizing Sustainable Tourism at Cekungan Bandung: The Role of Generation Z - Kurniasyifa Oktariyana Salsabira; Vany Octaviany (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to measure the behavior of Generation Z towards sustainable tourism in the Cekungan Bandung area, which is facing alarming conditions such as increasing temperatures, decreasing reserves of clean and healthy water, and increasing levels of environmental pollution. The research method applied is a qualitative approach with in-depth interviews involving respondents from Generation Z. This research focuses on the Cekungan Bandung area, a popular tourist destination in Indonesia. The study results indicate that Generation Z has shown awareness of the importance of implementing sustainable tourism. Even so, it was found that there was a need for further coaching to strengthen their attitudes and behavior in supporting sustainable tourism. The implications of this research are expected to support sustainable tourism goals by optimizing economic, environmental, and social benefits while effectively reducing the negative impacts that may arise